An Evaluation of the New Curriculum for German Language Teacher Education Programs in View of Core Competences - (:unkn) unknown (ISTANBUL UNIV, FAC LETTERS, 2020)
The aim of this study is to examine Turkey's new curriculum for German language teacher education in view of knowledge and skills related to core competences. For this aim, core competences identified in the EAQUALS Framework for Language Teacher Training and Development are specified and compared with domain - specific subjects in the new curriculum. Suggestions are then made to curriculum developers and practitioners on the basis of these findings. The study relies on qualitative research methods, specifically the application of document analysis to both texts. For this purpose, relevant knowledge and skills are categorized into key phases of ''planning, performing and assessing and evaluating. After categorization, domain - specific subjects of the new curriculum are specified, their contents examined and compared with the descriptions in the framework. This reveals that knowledge of the Common European Framework for Languages is absent from the curriculum. Also, subject contents in the planning phase differ from the framework. Furthermore, the essential subjects Material Evaluation in German Language Teaching and New Technologies in German Language Teaching are only elective. The compulsory subject Preparing Tests in German Language Teaching covers all knowledge areas defined in the framework. It is thus suggested that the elective subjectEvaluating In-Class Learning be removed and that Material Evaluation in German Language Teaching and New Technologies in German Language Teaching be made compulsory. Finally, further revision of subject content in the planning phase is strongly advised.
Keywords: Teacher education; language teaching; curriculum; foreign language; competence